Plague Vaccine Development: Current Research and Future Trends - Verma, Shailendra Kumar; Tuteja, Urmil (Frontiers in Immunology, 2016)
Plague is one of the world’s most lethal human diseases caused by Yersinia pestis, a Gram negative bacterium. Despite overwhelming studies for many years worldwide, there is no safe and effective vaccine against this fatal disease. Inhalation of Y. pestis bacilli causes pneumonic plague, a fast growing and deadly dangerous disease. F1/LcrV-based vaccines failed to provide adequate protection in African Green monkey model in spite of providing protection in mice and cynomolgus macaques. There is still no explanation for this inconsistent efficacy and scientists leg behind to search reliable correlate assays for immune protection. These paucities are the main barriers to improve the effectiveness of plague vaccine. In the present scenario, one has to pay special attention to elicit strong cellular immune response in developing a next-generation vaccine against plague. Here, we review the scientific contributions and existing progress in developing subunit vaccines, the role of molecular adjuvants; DNA vaccines; live delivery platforms and attenuated vaccines developed to counteract virulent strains of Y. pestis.